2012
DOI: 10.1371/journal.pone.0040058
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Macrophages into Organotypic Co-Cultures: A 3D In Vitro Model to Study Tumor-Associated Macrophages

Abstract: Tumor progression is controlled by signals from cellular and extra-cellular microenvironment including stromal cells and the extracellular matrix. Consequently, three-dimensional in vitro tumor models are essential to study the interaction of tumor cells with their microenvironment appropriately in a biologically relevant manner. We have previously used organotypic co-cultures to analyze the malignant growth of human squamous cell carcinoma (SCC) cell lines on a stromal equivalent in vitro. In this model, SCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 41 publications
3
88
0
1
Order By: Relevance
“…In collagen gels, monotypic or heterotypic cultures can be developed, thereby increasing the possibility of better mirroring the in vivo conditions by integrating tumor's neighboring cell types [122]. Culture of fibroblasts in collagen gels have allowed a better understanding of the reciprocal interactions between cells and ECM, and, namely, the regulation of cell behavior mediated by the mechanical properties of ECM [123].…”
Section: Mimicking the Ecmmentioning
confidence: 99%
“…In collagen gels, monotypic or heterotypic cultures can be developed, thereby increasing the possibility of better mirroring the in vivo conditions by integrating tumor's neighboring cell types [122]. Culture of fibroblasts in collagen gels have allowed a better understanding of the reciprocal interactions between cells and ECM, and, namely, the regulation of cell behavior mediated by the mechanical properties of ECM [123].…”
Section: Mimicking the Ecmmentioning
confidence: 99%
“…In a study with squamous carcinoma cells, M2 macrophages together with fibroblasts enhance the invasion rate of cancer cells compared to fibroblasts alone (Linde et al, 2012). In a similar manner, the combined presence factors, which all are associated with invasion, metastasis and ECM degradation (Goswami et al, 2005, Baran et al, 2009, Kessenbrock et al, 2010, Kuwada et al, 2003, Lesina et al, 2011.…”
Section: Discussionmentioning
confidence: 86%
“…The organotypic model has previously displayed favourable results for visualisation of cancer cell invasion and interplay with the local microenvironment (Froeling et al, 2009, Linde et al, 2012. The desmoplastic stroma produced by pancreatic stellate cells has been shown to create a treatment barrier around the tumour, limiting bioavailability of drugs (Jaster and Emmrich, 2008, Erkan et al, 2012, Whatcott et al, 2015.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we can determine the cells/signals that are most responsible for biasing the immune cell population into the immune-suppressing state. From the work by Linde et al [49], cancer cells alone can bias macrophages into the M2-like state (not immune-promoting) and fibroblasts can further speed up the process. Introducing the T cells would then test whether CD4 + Th1 and CD8 + T cells can help the co-culture system to remain stable in the immune-promoting state and whether fibroblasts, together with cancer cells, may revert this effect and polarize the immune cell population into the immune-suppressing state.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Linde et al [49] showed that during three-week long organotypic co-culture of cancer cells and unpolarized macrophages, the percentage of macrophages with a protein maker, which is usually expressed on M 2 -like macrophage, gradually elevates. For the co-cultures with additional fibroblasts, the percentage of M 2 -like macrophages increases faster compared to the co-cultures with cancer cells and macrophages only.…”
Section: Mathematical Models To Investigate the Interactions In Simplmentioning
confidence: 99%